PENYELESAIAN SENGKETA PERTANAHAN MELALUI PROSES MEDIASI PADA KANTOR PERTANAHAN KABUPATEN KEPAHIANG PERSPEKTIF HUKUM ISLAM - Mardalena, Eva (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: The purpose of this study is to describe the process of resolving land disputes through the mediation process at the Land Office of Kepahiang Regency and based on Islamic law. As well as describe the factors that become obstacles and obstacles in the defense dispute resolution process. The type of research carried out is qualitative-empirical research by examining documentation and interviewing informants. This study concludes that 1) The process of resolving land disputes through mediation at the Kepahiang District Land Office has been carried out in accordance with the applicable provisions, namely the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 21 of 2020. Where in the implementation of mediation, the parties involved The dispute is facilitated by the Land Office of Kepahiang Regency to be able to resolve disputes that occur, by way of deliberation to get the best solution or “win-win solution”. If in mediation no peace agreement is reached between the two disputing parties, the Kepahiang District Land Office will provide recommendations for resolving the dispute through litigation or court. 2) Settlement of land disputes through mediation according to Islamic law perspective, namely through tahkim, where the implementation is by summoning Settlement of land disputes through mediation according to Islamic law perspective, namely through tahkim, where the implementation is by summoning the two disputing parties and mediated by a hakam (mediator) to find a peace agreement between the disputing parties. 3) In the implementation of land dispute resolution mediation, there are obstacles and obstacles, including the absence of parties who do not have good intentions to take advantage of the mediation process, uncooperativeness of one or both parties when a call is made for the implementation of mediation, and the lack of human resources in the Section. Control and Handling of Disputes at the Land Office of Kepahiang Regency, sothat it can hinder the settlement of dispute cases that have been registered at the Kepahiang Regency Land Office. Keywords: Land Disputes, Mediation, Islamic Law Perspective Abstrak: Tujuan penelitian ini yaitu untuk mendiskripsikan proses penyelesaian sengketa pertanahan melalui proses mediasi pada Kantor Pertanahan Kabupaten Kepahiang dan berdasarkan hukum Islam. Serta mendiskripsikan faktor-faktor yang menjadi hambatan dalam proses penyelesaian sengketa pertahan. Jenis penelitian yang dilakukan yaitu penelitian kualitatif-empiris dengan cara meneliti dokumentasi dan mewawancari informan.Penelitian ini menyimpulkan bahwa 1) Proses penyelesaian sengketa pertanahan melalui mediasi pada Kantor Pertanahan Kabupaten Kepahiang telah dilaksanakan sesuai dengan kententuan yang beraku yaitu Peraturan Menteri Agraria dan Tata Ruang/ Kepala Badan Pertanahan Nasional Nomor 21 Tahun 2020. Dimana dalam pelaksannaan mediasi, pihak-pihak yang bersengketa difasilitasi oleh Kantor Pertanahan Kabupaten Kepahiang untuk dapat menyelesaikan sengketa yang terjadi, dengan cara musyawarah untuk mendapatkan solusi yang terbaik atau “win-win solution”. Jika dalam mediasi tidak tercapai kesepakatan perdamaian antara kedua belah pihak yang bersengketa, maka Kantor Pertanahan Kabupaten Kepahiang akan memberikan rekomendasi untuk penyelesaian sengketa tersebut melalui jalur litigasi atau peradilan. 2) Penyelesaian sengketa pertanahan melaui mediasi menurut persektif hukum Islam yaitu melalui tahkim, dimana pelaksanaannya dengan memanggil kedua belah pihak yang bersengketa dan dimediasi oleh seorang hakam (mediator) untuk menemukan kesepakatan perdamaian antara pihak yang bersengketa. 3) Dalam pelaksanaan mediasi penyelesaian sengketa pertanahan terdapat hambatan dan kendala, antara lain tidak adanya pihak yang tidak memiliki itikad baik untuk memanfaatkan proses mediasi, tidak kooperatifnya salah satu atau kedua belah pihak saat dilakukan pemanggilan untuk pelaksanaan mediasi, serta kurangnya sumber daya manusia di Seksi Pengendalian dan Penanganan Sengketa pada Kantor Pertanahan Kabupaten Kepahiang, sehingga dapat menghambat penyelesaian terhadap kasus sengketa yang telah terdaftar di Kantor Pertanahan Kabupaten Kepahiang. Kata kunci :Sengketa Pertanahan, Mediasi, Perspektif Hukum Islam